Development of Batik Modul Based on Local Culture of North Sumatra, Indonesia - Farihah Farihah; Halimul Bahri; Surniati Chalid; Yudhistira Anggraini (IJORER : International Journal of Recent Educational Research, 2022)
This study aims to develop teaching materials in the form of local culture-based batik moduls that can be used as the development of Medan batik motives at Ardhina Batik Medan. This study uses the Research and Development (R&D) research method and the research model uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the study show that the results of the modul feasibility test according to 6 experts. The results of the data analysis carried out stated that the batik modul based on the local culture of North Sumatra at Ardhina Batik Medan was suitable for use with the "very good" criteria from material experts with an average score of 3 experts, namely 131 or 90.8%, and 3 media experts with a mean score of 141 or 88.5% in the very good category. Thus it can be concluded that the batik modul can be used in learning as well as a means to preserve and develop Medan's typical batik motives.With this modul, students can get to know batik and the process of batik as well as modify the typical motives of several regions into one combination motif (stylization).